2008
DOI: 10.1080/10790268.2008.11753645
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training and Inspiratory Muscle Training in Spinal Cord Injury: A Systematic Review

Abstract: Objective: To provide a systematic review of the studies assessing exercise training and inspiratory muscle training (IMT) in individuals for the improved respiratory function of patients with spinal cord injury (SCI). Methods: Thirteen studies (5 exercise training, 8 IMT) were identified. Articles were scored for their methodological quality using the Physiotherapy Evidence Database scores and Downs and Black tools for randomized and nonrandomized studies, respectively. Conclusions were based on the most rigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
13

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 34 publications
0
25
0
13
Order By: Relevance
“…Previous attempts at systematically reviewing the research to evaluate the effect of RMT in patients with SCI [9][10][11] have reported that heterogeneity, in terms of research design, participant characteristics, training techniques used and outcomes measured, has prohibited meta-analysis. We recently published a Cochrane review (including meta-analysis) of RMT in cervical SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts at systematically reviewing the research to evaluate the effect of RMT in patients with SCI [9][10][11] have reported that heterogeneity, in terms of research design, participant characteristics, training techniques used and outcomes measured, has prohibited meta-analysis. We recently published a Cochrane review (including meta-analysis) of RMT in cervical SCI.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, review articles on respiratory muscle training in individuals with SCI showed that most studies were of low methodological quality and that there are not yet enough data to show a clear effect of respiratory muscle training on respiratory function, respiratory complications, or quality of life. 8,9 Additionally, there exist different methods for respiratory muscle training in clinical practice, which can roughly be scaled in respiratory resistance (strength) and respiratory muscle endurance training methods. To our knowledge, there exists no study that compared the effects of these 2 basically different respiratory muscle training methods in individuals with SCI.…”
mentioning
confidence: 99%
“…Three studies were qualified as level 1 evidence using the modified Sackett's criteria. 10 Outcome measures linked to the ICF A total of 374 outcomes were extracted from the selected studies. For those outcome measures that belong to multi-item surveys, we attempted to retrieve survey documents to include as many ICF codes as possible.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…8 Studies have shown increasing physical activity may be beneficial for individuals with SCI. 4,9 Previous reviews pertaining to exercise and SCI have focused primarily on improvements in physical capacity measures, [9][10][11] without relating the outcome measures to the categories and components of the International Classification of Functioning, Disability and Health (ICF). 12 A recent review that linked outcome measures to the ICF in people with SCI reported a large number of outcomes were related to 'Body Structures' and 'Body Functions' components.…”
Section: Introductionmentioning
confidence: 99%